Cultural materialist reading: visualizing dominant ideologies and dissident discourses in the creative graphic panels of Munnu: A Boy from Kashmir - Selvam, Manjula; Mukherjee, Sangeeta (Creativity Studies, 2023)
One of the prominent theories of cultural studies is cultural materialism, which has its base on the theory of Marxism. Much of the research work done regarding cultural materialism is on Renaissance literature; the development of the theory itself is through the studies conducted on the plays of William Shakespeare, who is one of the epitomes of Renaissance literature. This paper aims to be a unique cultural materialist reading done on a graphic novel based on Kashmir, Indian subcontinent. Kashmir is one of the most desired lands on Earth; it has also been a land of contest right from 1947. This article attempts to explore Malik Sajad’s reflection of the Kashmiri society by analyzing and discussing graphic panels from Munnu: A Boy from Kashmir (originally published in 2015) in the light of cultural materialism. Since cultural materialism admits that a text mirrors the socio-cultural and political life of a society; it has been used for interpreting this Kashmir-based graphic novel which is a blend of image and words. This graphic memoir offers a unique narration of the political and societal lives of Kashmiris through the creative deployment of an anthropomorphic metaphor. This study shows how Sajad graphically reflects the dominant ideology and dissident discourses in these panels.